Evaluation of Policy Implementation (G. Edward III Theory) on the Stunting Prevention and Treatment Program at Waena Health Center, Jayapura City Papua Province - Kogoya, Yuli; Togodly, Arius; Tingginehe, Rosmin M.; Ruru, Yakob; Bouway, Dolfinus; Mediati, Novita (Formosa Journal of Science and Technology, 2024)
The aim of this research is to determine the evaluation of policy implementation (G. Edward III Theory) in the stunting prevention and management program at the Waena Health Center, Jayapura City, Papua Province. This type of research is qualitative.The research instrument used an interview guide and was analyzed qualitatively. The bureaucratic structure of the Waena Community Health Center does not have a bureaucratic structure or bureaucratic structure design, but in its implementation it refers to Standard Operating Procedures (SOP) in accordance with technical guidelines or instructions. Obstacles are still low knowledge about stunting and the community economy as well as cross-sector cooperation and coordination that is still not strong enough in handling stunting.